Determinasi Budaya dan Pentingnya Domestikasi Teknologi Dalam Dakwah - Hariri, Muh. Mirwan (Universitas Nahdlatul Ulama Blitar, 2023)
This study aims to explain more deeply the concept of cultural determination to determine the direction of da'wah in the future. This article is a qualitative type with documentation as data collection methods. Cultural determination is a concept inherent in technological determination. In the concept of technological determination, it explains that technology is not only defined as a tool or media that helps people carry out activities to make it easier. But more deeply, technology can affect the pattern of people's lives both from the mindset and behavior in all aspects. Changes due to technology and inherent in humans are called culture. Technology can shift one culture into another culture in accordance with technological developments or trends. In short, technology comes with a particular purpose or interest. In the context of da’wah, determination can have various and unconscious impacts. Then it will make da'wah can be controlled by the existence of technology itself. So, in the world of da'wah, a domestication process is needed to control technology. In this study, the researcher describes three steps that can be taken to control technology, namely: identification, selection and da’wah innovation.